Songs About Social Classes and Their Presentation in Two Largest Latvian Folksong Editions. - KROGZEME-MOSGORDA, BAIBA (Folklore Studies / Tautosakos Darbai, 2020)
The article is focused on folksongs about social classes or the so-called social songs, which differ from other Latvian folksongs with their historical content, which has been interpreted from different perspectives in the two largest Latvian folksong editions. In the arrangement of social songs for the first complete folksong edition Latvju dainas (1894-1915) the ideas of the Latvian National Awakening were highlighted, whereas the chapter on social songs in the academic edition Latviešu tautasdziesmas (1979-2018) demonstrates the impact of Soviet ideology. The article also reveals the role of compilers' personalities in the selection, classification, and interpretation of social songs.